Estrutura genética populacional de Brycon hilarii (Characidae) da sub-bacia do Rio Miranda, e seu significado para programas de conservação - Sanches, Alexandra (2007)
Brycon hilarii (subfamily Bryconinae, Characidae), popularly known as piraputanga, is a migratory fish species distributed throughout the entire Paraguay River basin and largely appreciated for its meat quality as well as for fishing, besides being the main species of touristic value in the Bonito region (MS, Brazil). Considering the lack of information on the population genetic structure of these fish, the objective of the present study was to analyze, through the use of microsatellite markers, the distribution of the genetic variability in Brycon hilarii collected in different localities of the Miranda River sub-basin (Paraguay basin) in the Bonito region (MS). For such an end, at first a total of seven polymorphic microsatellite loci capable of producing a considerable genetic variation was prospected (among di-, tri- and tetranucleotides), with their also being efficient in the heterologous amplification for five other species of the genus. In the populational analysis of B. hilarii, the different samples presented very similar genetic diversity levels. Through the FST values, gene and genotype differentiation tests and Bayesian analysis, it was possible to verify (1) the existence of at least two genetic populations of Brycon hularii coexisting in the sampled range, despite being a potentially mobile species; and (2) that only the fish from a reproductive stock were genetically differentiated from the other samples, representing a putative population unit. It is possible that in the reproductive season the more genetically homogeneous individuals organize themselves into a population genetic unit or a reproductive stock, aiming the maintenance of their genetic integrity. These results on the genetic structure of B. hilarii constitute tools of extreme importance considering they can aid the understanding of the behavior and biology of these fish, contributing to fish management and species conservation programs.